AKIBAT HUKUM TERHADAP SERTIFIKAT HAK ATAS TANAH YANG TUMPANG TINDIH: Studi Kasus Putusan Nomor 32/G/2023/PTUN SBY - Tjoe Kang Long; Widyawati Boediningsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Legal efforts to facilitate referrals to plots of land so that good land management can be carried out. After the land registration has been completed according to the stages carried out, a Principal Rights Certificate is issued. This is proof of ownership and is considered strong evidence of the physical and legal data contained therein as long as the physical and legal data is still maintained. The data is in accordance with information from relevant survey documents and land legal documents. A certificate as proof of land ownership after being registered at the Land Office of course brings legal certainty to the holder. However, in fact there are several cases where the certificates overlap, such as in the case that was decided in decision number 32/G/2023/PTUN SBY ​​between Sri Wulandari and the Head of the Batu City Land Office and I Made Artawan. Legal certainty regarding land ownership is by registering the land owned by each person, because based on Article 1 paragraph (1) of the Basic Agrarian Law, by registering the land we own, this guarantees legal certainty for the land owner and is proven by the issuance of a land title certificate. This land ownership certificate has strong evidentiary value as long as the land procurement and registration is carried out according to established procedures and there are no clerical defects in the land registration. Article 32 (2) PP Regulation Number 24 of 1997.